2022
DOI: 10.3389/fneur.2022.908468
|View full text |Cite|
|
Sign up to set email alerts
|

A Prosperous Application of Hydrogels With Extracellular Vesicles Release for Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one of the leading causes of disability worldwide, becoming a heavy burden to the family and society. However, the complexity of the brain and the existence of blood-brain barrier (BBB) do limit most therapeutics effects through simple intravascular injection. Hence, an effective therapy promoting neurological recovery is urgently required. Although limited spontaneous recovery of function post-TBI does occur, increasing evidence indicates that exosomes derived from stem cells p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 117 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Exosome readily crosses the BBB and has the potential to specifically deliver molecules to CNS 11 . Recently, studies have revealed the effective role of exosome in the diagnosis and treatments of CNS diseases such as TBI 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosome readily crosses the BBB and has the potential to specifically deliver molecules to CNS 11 . Recently, studies have revealed the effective role of exosome in the diagnosis and treatments of CNS diseases such as TBI 15 …”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, studies have revealed the effective role of exosome in the diagnosis and treatments of CNS diseases such as TBI. 15 It has been shown that HucMSC could provide neuroprotection after TBI. 16 However, the role of HucMSC-derived exosome in TBI has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Low-rigidity hydrogels with conductive properties have great potential as they can be specifically adapted for neuroelectrophysiology and biomechanics [ 26 ]. However, it is important to note that the swelling properties of hydrogels require special attention when applied to the central nervous system (CNS); because CNS injuries are often accompanied by tissue edema, the high swelling properties of hydrogels can lead to increased intracranial pressure and consequent secondary injury after hydrogel injection [ 226 ].…”
Section: Tissue-specific Applications Of Ev-loaded Hydrogelsmentioning
confidence: 99%
“…The brain is a complex tissue of the central nervous system which has the function of integrating and regulating signals and information in the nervous system along with the spinal cord [ 40 ]. Patients with traumatic brain injury are susceptible to permanent neurological deficits, which influence their daily lives [ 68 ]. Traumatic brain injury can be classified into primary injury and secondary injury.…”
Section: The Nervous Systemmentioning
confidence: 99%